Thin CdTe Layers Deposited by a Chamberless Inline Process using MOCVD, Simulation and Experiment - Giray Kartopu (Applied Sciences, 2020)
The deposition of thin Cadmium Telluride (CdTe) layers was performed by a chamberless metalorganic chemical vapour deposition process, and trends in growth rates were compared with computational fluid dynamics numerical modelling. Dimethylcadmium and diisopropyltelluride were used as the reactants, released from a recently developed coating head orientated above the glass substrate (of area 15 × 15 cm2). Depositions were performed in static mode and dynamic mode (i.e., over a moving substrate). The deposited CdTe film weights were compared against the calculated theoretical value of the molar supply of the precursors, in order to estimate material utilisation. The numerical simulation gave insight into the effect that the exhaust’s restricted flow orifice configuration had on the deposition uniformity observed in the static experiments. It was shown that > 59% of material utilisation could be achieved under favourable deposition conditions. The activation energy determined from the Arrhenius plot of growth rate was ~ 60 kJ/mol and was in good agreement with previously reported CdTe growth using metalorganic chemical vapour deposition (MOCVD). Process requirements for using a chamberless environment for the inline deposition of compound semiconductor layers were presented.